High-strength and high-hardness multicomponent alloy titanium-based composite material and preparation method thereof
By using the coordinated strengthening of multi-alloy matrix and rare earth oxides with hard phase in titanium-based composite materials, combined with vacuum suspension smelting and hot rolling processes, high-strength and high-hard multi-alloy titanium-based composite materials are prepared, and the hardness is further improved through ionic nitriding treatment, solving the problem of insufficient strength and hardness of existing materials under harsh environments, and achieving the material requirements of high-performance mechanical components.
Patent Information
- Application Number
- CN202411995547.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Under harsh environments, the strength and hardness of existing titanium-based composite materials are difficult to meet the performance requirements of high-temperature, high-pressure and high-speed mechanical components on materials.
High-strength and high-hard multi-alloy titanium-based composite materials are prepared by vacuum suspension smelting and hot rolling processes, and ionic nitriding treatment is carried out to further improve hardness.
It achieves the improvement of the strength and hardness of the material under harsh environments, enhances fatigue resistance and thermal stability, and makes the material suitable for the manufacturing of high-performance mechanical components.
Smart Images

Figure CN119776691A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite materials, and more specifically to a high-strength and high-hardness multi-component alloy titanium-based composite material and a preparation method thereof. Background Art
[0002] As various industries continue to pursue high-precision and high-efficiency processing and the performance requirements for materials continue to increase. For example, in the milling of automobile engine cylinders, high-strength and high-hardness materials such as carbide tools are needed to ensure processing accuracy and tool life. In mold manufacturing, in order to produce parts with complex shapes, high precision and large batches, the mold material must have sufficient strength and hardness. For example, injection molds are used to produce high-precision plastic parts, which require high-strength and high-hardness mold steel. In the field of aerospace, in order to reduce the weight of aircraft to improve fuel efficiency and ensure the structural strength of the fuselage, high-strength and high-hardness carbon fiber composite materials are needed to manufacture wings, fuselages and other components. In particular, the working environment of aircraft engines is extremely harsh. For example, high-temperature, high-pressure, and high-speed turbine blades require high-strength and high-hardness materials to withstand the impact of high-temperature gas and maintain a stable working state. In the field of new energy, such as wind power generation, in order to improve the strength and wind erosion resistance of wind turbine blades, high-strength and high-hardness fiber-reinforced composite materials are also needed. In addition, the body and track materials of high-speed trains also require high-strength and high-hardness properties to cope with the huge pressure and friction during high-speed driving.
[0003] Titanium alloys are widely used in aircraft engines, fuselage structures, landing gear and other parts because of their advantages such as high strength, low density, high temperature resistance and corrosion resistance. For example, engine compressor blades, disks and other components can work stably in high temperature environments and improve engine performance. However, facing more demanding thermal cycles and mechanical environments, the strength and hardness of materials are extremely high. Therefore, there is an urgent need to develop high-strength and high-hardness titanium-based composite materials with better performance to meet the requirements for material strength and hardness in harsh environments. Summary of the invention
[0004] The present application provides a high-strength and high-hardness multi-element alloy titanium-based composite material and a preparation method thereof to meet the requirements for the strength and hardness of the material in harsh environments.
[0005] The implementation process of the present invention is as follows:
[0006] In a first aspect, a method for preparing a high-strength and high-hardness multi-component alloy titanium-based composite material is provided, comprising the following steps: (S1) configuring raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy material; (S2) subjecting the alloy material to vacuum suspension melting to obtain a titanium-based composite ingot; (S3) subjecting the titanium-based composite ingot to at least four hot rolling steps in the (α+β) phase region to obtain a high-strength and high-hardness multi-component alloy titanium-based composite material.
[0007] Furthermore, the high-strength and high-hardness multi-element alloy titanium-based composite material is subjected to ion nitriding treatment, and the hardness of the obtained titanium-based composite material is further improved.
[0008] Further, in step (S1), the element composition of the matrix is Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo 1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the balance is Ti; the reinforcing phase includes La 2 O 3 , also including TiB and / or TiC.
[0009] Furthermore, the mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
[0010] Furthermore, in step (S2), the specific process of the vacuum suspension smelting includes the following steps: (S2.1) placing the alloy material in a crucible; (S2.2) evacuating the furnace of a vacuum water-cooled copper crucible suspension smelting furnace, filling it with argon, and turning on the power; (S2.3) smelting at a power of 70 to 140 kW, and then refining at a power of 130 to 140 kW; (S2.4) turning the alloy over and repeating the smelting and refining process at least 5 times. After the refining is completed, the furnace is naturally cooled, the gas is released from the furnace, and a titanium-based composite material ingot is obtained.
[0011] Furthermore, in step (S3), the starting rolling temperature of each hot rolling pass is 1200-1250K, and the final rolling temperature is 1175-1200K.
[0012] Furthermore, in step (S3), an intermediate annealing treatment is performed between hot rolling passes at a temperature of 1190 to 1220 K for 0.5 to 6 hours.
[0013] Furthermore, in step (S1), the elements Ti, Al, Nb, Fe, Mo, V, and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy, and sponge zirconium respectively; TiB, TiC, La in the reinforcement phase 2 O 3 They are added in the form of titanium diboride, graphite powder and lanthanum oxide respectively.
[0014] Further, the titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown in the following formula: Ti+TiB 2 =2TiB, Ti+C=TiC.
[0015] Furthermore, the vacuum degree in step (S2.2) is 3.5×10 -2 ~4×10 -2 Pa, filled with argon 0.07~0.09MPa.
[0016] Furthermore, in the step (S2.3), the smelting process is carried out at powers of 70-80kw, 90-100kw, 110-120kw, and 130-140kw in sequence, and then refined at a power of 130-140kw.
[0017] In a second aspect, a high-strength and high-hardness multi-component alloy titanium-based composite material prepared by the method described in any one of the first aspects is provided, comprising a matrix and a reinforcement phase, wherein the mass percentage of the element composition of the matrix is Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo 1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the remainder is Ti; the reinforcement phase comprises La 2 O 3 , also includes TiB and / or TiC, and the mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
[0018] The positive effects of the present invention are as follows: (1) The preparation method of the high-strength and high-hardness multi-component alloy titanium-based composite material of the present invention is simple, easy to operate, and easy to industrialize and apply. (2) The titanium-based composite material of the present invention adopts a multi-component alloy matrix to reduce the phase transition point temperature and supplement the strength; and the addition of La 2 O 3 The reinforcement phase composed of TiB and / or TiC achieves synergistic strengthening with the matrix, wherein the rare earth oxide La 2 O 3 It is beneficial to refine the grains of the composite material, improve fatigue resistance, improve thermal stability, and ultimately obtain a high-strength and high-hardness multi-element alloy titanium-based composite material.
[0019] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate one or more embodiments of the present application and, together with the description, serve to explain the principles of the present application and to enable one of ordinary skill in the relevant art to make and use the present application.
[0021] Figure 1 is a process flow chart of the method of the present invention;
[0022] Figure 2 Engineering stress-strain curves from TMC0-60 to TMC6-60;
[0023] Figure 3 Optical microscope images of TMC0-TMC6 as-cast;
[0024] Figure 4 SEM images of TMC0-TMC6 as-cast;
[0025] Figure 5 Optical microscope images of TMC0-TMC6 after hot rolling;
[0026] Figure 6 The SEM images of TMC0-TMC6 after hot rolling;
[0027] Figure 7 Optical microscope images of TMC0-60 to TMC6-60;
[0028] Figure 8 SEM images of TMC0-60 to TMC6-60. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments may be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; rather, the description of these embodiments is intended to make the present application more comprehensive and complete and to fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a deeper understanding of the embodiments of the present application.
[0030] The present invention provides a method for preparing a high-strength and high-hardness multi-component alloy titanium-based composite material, which has the characteristics of being simple, easy to operate, and easy to industrially apply. Figure 1 As shown, the specific steps include:
[0031] (S1) preparing raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy material;
[0032] The element composition of the matrix is Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo 1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the balance is Ti.
[0033] The reinforcement phase includes La2 O 3 , also includes TiB and / or TiC, and the mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
[0034] The elements Ti, Al, Nb, Fe, Mo, V, and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy, and sponge zirconium respectively; TiB, TiC, La in the reinforcement phase 2 O 3 Titanium diboride, graphite powder and lanthanum oxide are added respectively. The titanium diboride and graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction. The in-situ autogenous reaction is shown in the following formula: Ti+TiB 2 =2TiB, Ti+C=TiC.
[0035] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0036] The specific process of the vacuum suspension melting comprises the following steps:
[0037] (S2.1) placing alloy material in a crucible;
[0038] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 ~4×10 -2 Pa, fill with argon 0.07~0.09MPa, turn on the power;
[0039] (S2.3) melting at 70-80 kW, 90-100 kW, 110-120 kW, and 130-140 kW for 4-6 minutes respectively, and then refining at 130-140 kW for 4-6 minutes;
[0040] (S2.4) The alloy is turned over and the melting and refining process is repeated at least 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0041] (S3) hot rolling the titanium-based composite material ingot in the (α+β) phase region for at least four times to obtain a high-strength and high-hardness multi-element alloy titanium-based composite material.
[0042] The starting temperature of each hot rolling pass is 1200-1250K, the final rolling temperature is 1175-1200K, an intermediate annealing treatment of 0.5-6h at 1190-1220K is performed between hot rolling passes, and the hot rolling deformation is 60%-80%.
[0043] The high-strength and high-hardness multi-element alloy titanium-based composite material obtained after hot rolling of the present invention is further improved in hardness by ion nitriding treatment. The specific process is to put the hot-rolled rod of the titanium-based composite material into a glow ion nitriding furnace, set the voltage to 400-500V, the temperature to 400-900°C, and the heating rate to 20-25°C / min, and then introduce nitrogen. When the temperature reaches 400-900°C, introduce hydrogen (according to the volume ratio of nitrogen to hydrogen of 1:3) into the glow ion nitriding furnace until the pressure is 200-250Pa, and perform ion nitriding for 5-20 hours. After cooling, the titanium-based composite material after ion nitriding treatment is obtained.
[0044] The present invention also provides a high-strength and high-hardness multi-component alloy titanium-based composite material prepared by the above method, comprising a matrix and a reinforcement phase, wherein the element composition weight percentage of the matrix is Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the balance is Ti;
[0045] The reinforcement phase includes La 2 O 3 , also includes TiB and / or TiC, and the mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
[0046] The titanium-based composite material of the present invention adopts a multi-element alloy matrix to reduce the phase transition point temperature and supplement the strength; and La is added 2 O 3 Together with TiB and / or TiC, they form a reinforcing phase and achieve synergistic strengthening with the matrix. 2 O 3 It is beneficial to refine the grains of the composite material, improve fatigue resistance, improve thermal stability, and ultimately obtain a high-strength and high-hardness multi-element alloy titanium-based composite material.
[0047] The muffle furnace described in the present invention adopts ZY-1200 muffle furnace. In addition to the muffle furnace of the model described in the present invention, muffle furnaces of other manufacturers and models can also be used, as long as the effect of heating and heat preservation can be achieved. The hot rolling mill can use any manufacturer and model of hot rolling mill, as long as the hot rolling process described in the present invention can be carried out. In the smelting and hot rolling process of the matrix alloy and the titanium-based composite material of the present invention, the α+β~β phase transition temperature plays an important reference role. In addition, the presence of elements such as aluminum, vanadium, zirconium, and iron in the titanium-based composite material will affect its α+β~β phase transition temperature, and impurity elements such as carbon, hydrogen, oxygen, and nitrogen will also affect its phase transition temperature. In order to provide a scientific basis for subsequent experimental research, the α+β~β phase transition temperature of the matrix alloy TMC0 of comparative example 1 was measured by differential scanning calorimetry (DSC) to be 950°C, and the α+β~β phase transition temperature of the titanium-based composite material of embodiment 1 was measured by continuous heating metallographic method to be between 1000 and 1025°C.
[0048] The specifications of the raw materials involved in the present invention are shown in Table 1.
[0049] Table 1 Specifications of raw materials used in the experiment
[0050]
[0051]
[0052] Among them, the density of TiB is 4.50g / cm 3 The density of TiC is 4.99 g / cm 3 , La 2 O 3 The density is 6.51g / cm 3 The relative atomic masses of each element required for the calculation are: B: 10.81, C: 12.01, Ti: 47.87, O: 16.00, La: 138.91.
[0053] Comparative Example 1 Matrix alloy TMC0
[0054] The base alloy includes the following element compositions in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr 0.8% and the balance Ti.
[0055] The preparation method of the substrate comprises the following steps:
[0056] (S1) According to the mass percentage of the elemental components of the base alloy, 821.91 g of sponge titanium, 44.33 g of high-purity aluminum, 43.40 g of niobium-titanium alloy (Ti-53Nb), 16 g of iron particles, 21.67 g of vanadium-aluminum alloy (Al-60V), 44.69 g of titanium-molybdenum alloy (Ti-32Mo), and 8 g of sponge zirconium are added to obtain a base alloy material.
[0057] (S2) obtaining a base alloy ingot by vacuum arc melting the base alloy material;
[0058] The parameters of the vacuum arc melting process are as follows:
[0059] (S2.1) placing a base alloy material in a crucible;
[0060] (S2.2) performing the first vacuum arc melting of the base alloy material, wherein the vacuum degree in the vacuum arc melting furnace is evacuated to <9 Pa, the melting current range is 700-2300 A, the arc stabilization current range is 2-5 A, the arc stabilization voltage range is 12-35 V, and the melting time is 5 minutes;
[0061] (S2.3) The alloy is turned over and vacuum arc melted for the second time. The vacuum degree in the vacuum arc melting furnace is evacuated to <9Pa. The melting current range is 600-4300A. The arc stabilization current range is 2-5A. The arc stabilization voltage range is 12-35V. The melting time is 5 minutes. After the melting is completed, the furnace is naturally cooled, the gas is released from the furnace, and the matrix alloy ingot is obtained.
[0062] (S3) First, use wire cutting to cut a cylindrical casting on the base alloy ingot; then evenly apply Ti-1200 high-temperature anti-oxidation coating on the surface of the casting to reduce high-temperature oxidation. After drying, put the casting into a hot rolling mill for six hot rolling passes. The starting rolling temperature of each hot rolling pass is 1250K, and the final rolling temperature is 1200K. An intermediate annealing treatment is performed between hot rolling passes at 1220K for 1 hour. The hot rolling deformation is 80%, and a hot-rolled rod of the base alloy is obtained, which is numbered TMC0. The density of the base alloy TMC0 needs to be tested by the Archimedes drainage method, and the final density of the base alloy is measured to be 4.61g / cm 3 .
[0063] Example 1 High-strength and high-hardness multi-element alloy titanium-based composite material TMC1
[0064] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0065] The reinforcing phase is TiB and La 2O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 2.74%, and La 2 O 3 The mass percentage is 0.285%.
[0066] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0067] (S1) adding raw materials of titanium sponge 808.23g, high-purity aluminum 43g, niobium titanium alloy (Ti-53Nb) 42.08g, iron particles 15.52g, vanadium aluminum alloy (Al-60V) 21.01g, titanium molybdenum alloy (Ti-32Mo) 43.34g, and zirconium sponge 7.76g according to the mass percentage of the element components of the matrix, and then adding reinforcing phase titanium diboride 16.20g and lanthanum oxide 2.86g to obtain an alloy material; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB.
[0068] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0069] The specific process of the vacuum suspension melting comprises the following steps:
[0070] (S2.1) placing alloy material in a crucible;
[0071] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0072] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0073] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0074] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC1.
[0075] Example 2 High-strength and high-hardness multi-element alloy titanium-based composite material TMC2
[0076] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0077] The reinforcing phase is TiC, La 2 O 3 The mass percentage of TiC in the titanium-based composite material is 2.75%, and the mass percentage of La 2 O 3 The mass percentage is 0.285%.
[0078] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0079] (S1) According to the mass percentage of the elemental components of the matrix, 818.94g of sponge titanium, 43g of high-purity aluminum, 42.08g of niobium-titanium alloy (Ti-53Nb), 15.51g of iron particles, 21g of vanadium-aluminum alloy (Al-60V), 43.33g of titanium-molybdenum alloy (Ti-32Mo), and 7.76g of sponge zirconium are added as raw materials, and then 5.53g of reinforcing phase graphite powder and 2.85g of lanthanum oxide are added to obtain an alloy material; the graphite powder is synthesized into TiC by in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+C=TiC.
[0080] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0081] The specific process of the vacuum suspension melting comprises the following steps:
[0082] (S2.1) placing alloy material in a crucible;
[0083] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0084] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0085] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0086] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC2.
[0087] Example 3 High-strength and high-hardness multi-element titanium-based composite material TMC3
[0088] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0089] The reinforcing phase is TiB, TiC and La 2 O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 1.33%, the mass percentage of TiC is 1.47%, and the mass percentage of La 2 O 3 The mass percentage is 0.285%.
[0090] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0091] (S1) adding raw materials of titanium sponge 813.75g, high-purity aluminum 42.96g, niobium titanium alloy (Ti-53Nb) 42.06g, iron particles 15.5g, vanadium aluminum alloy (Al-60V) 21g, titanium molybdenum alloy (Ti-32Mo) 43.31g, and zirconium sponge 7.75g according to the mass percentage of the elemental components of the matrix, and then adding reinforcing phase titanium diboride 7.86g, graphite powder 2.95g, and lanthanum oxide 2.86g to obtain an alloy material; the titanium diboride and graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB, Ti+C=TiC.
[0092] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0093] The specific process of the vacuum suspension melting comprises the following steps:
[0094] (S2.1) placing alloy material in a crucible;
[0095] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0096] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0097] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0098] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC3.
[0099] Example 4 High-strength and high-hardness multi-element titanium-based composite material TMC4
[0100] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0101] The reinforcing phase is TiB and La 2 O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 4.94%, and La 2 O 3 The mass percentage is 0.285%.
[0102] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0103] (S1) according to the mass percentage of the elemental components of the matrix, raw materials including sponge titanium 799.1g, high-purity aluminum 42.02g, niobium titanium alloy (Ti-53Nb) 41.13g, iron particles 15.16g, vanadium aluminum alloy (Al-60V) 20.53g, titanium molybdenum alloy (Ti-32Mo) 42.35g, and sponge zirconium 7.58g are added, and then reinforcing phase titanium diboride 29.27g and lanthanum oxide 2.86g are added to obtain an alloy material; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB.
[0104] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0105] The specific process of the vacuum suspension melting comprises the following steps:
[0106] (S2.1) placing alloy material in a crucible;
[0107] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0108] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0109] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0110] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC4.
[0111] Example 5 High-strength and high-hardness multi-element alloy titanium-based composite material TMC5
[0112] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0113] The reinforcing phase is TiC and La 2 O 3 The mass percentage of the reinforcing phase TiC in the titanium-based composite material is 5.45%, and La 2 O 3 The mass percentage is 0.285%.
[0114] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0115] (S1) According to the mass percentage of the elemental components of the matrix, 818.35g of sponge titanium, 41.79g of high-purity aluminum, 40.91g of niobium-titanium alloy (Ti-53Nb), 15.08g of iron particles, 20.42g of vanadium-aluminum alloy (Al-60V), 42.12g of titanium-molybdenum alloy (Ti-32Mo), and 7.54g of sponge zirconium are added as raw materials, and then 10.94g of reinforcing phase graphite powder and 2.85g of lanthanum oxide are added to obtain an alloy material; the graphite powder is synthesized into TiC through an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+C=TiC.
[0116] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0117] The specific process of the vacuum suspension melting comprises the following steps:
[0118] (S2.1) placing alloy material in a crucible;
[0119] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0120] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0121] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0122] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC5.
[0123] Example 6 High-strength and high-hardness multi-element alloy titanium-based composite material TMC6
[0124] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase. The matrix alloy includes the following elemental components in mass percentage: Al 5.3%, Nb 2.3%, Fe 1.6%, Mo 1.43%, V 1.3%, Zr0.8% and the balance is Ti.
[0125] The reinforcing phase is TiB, TiC and La 2 O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 2.47%, the mass percentage of the reinforcing phase TiC is 2.73%, and the mass percentage of La 2 O 3 The mass percentage is 0.285%.
[0126] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0127] (S1) adding raw materials of titanium sponge 804.35g, high-purity aluminum 43g, niobium titanium alloy (Ti-53Nb) 42.09g, iron particles 15.52g, vanadium aluminum alloy (Al-60V) 21.01g, titanium molybdenum alloy (Ti-32Mo) 43.34g, and zirconium sponge 7.76g according to the mass percentage of the elemental components of the matrix, and then adding reinforcing phase titanium diboride 14.60g, graphite powder 5.48g and lanthanum oxide 2.85g to obtain an alloy material; the titanium diboride and graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB, Ti+C=TiC.
[0128] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0129] The specific process of the vacuum suspension melting comprises the following steps:
[0130] (S2.1) placing alloy material in a crucible;
[0131] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0132] (S2.3) melting at 70kw, 90kw, 110kw and 130kw for 5 minutes respectively, and then refining at 130kw for 5 minutes;
[0133] (S2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0134] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1200K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1220K for 1h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC6.
[0135] Example 7 High-strength and high-hardness multi-element titanium-based composite material TMC7
[0136] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase, and the matrix alloy includes the following elemental components in mass percentage: Al 5%, Nb 2%, Fe 1.5%, Mo 1.4%, V 1.25%, Zr 0.8% and the balance is Ti.
[0137] The reinforcing phase is TiB and La 2 O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 2.7%, and La 2 O 3 The mass percentage is 0.32%.
[0138] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0139] (S1) adding raw materials of titanium sponge 818.88g, high-purity aluminum 40.41g, niobium titanium alloy (Ti-53Nb) 36.6g, iron particles 14.56g, vanadium aluminum alloy (Al-60V) 20.2g, titanium molybdenum alloy (Ti-32Mo) 42.43g, and zirconium sponge 7.76g according to the mass percentage of the elemental components of the matrix, and then adding reinforcing phase titanium diboride 15.96g and lanthanum oxide 3.2g to obtain an alloy material; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB.
[0140] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0141] The specific process of the vacuum suspension melting comprises the following steps:
[0142] (S2.1) placing alloy material in a crucible;
[0143] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 3.5×10 -2 Pa, fill with argon 0.07MPa, turn on the power;
[0144] (S2.3) melting at 75kw, 95kw, 115kw and 135kw for 4 minutes respectively, and then refining at 135kw for 4 minutes;
[0145] (S2.4) The alloy is turned over and the melting and refining process is repeated 6 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0146] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for six hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1250K, the final rolling temperature is 1175K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1200K for 0.5h. The hot rolling deformation is 80%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC7.
[0147] Example 8 High-strength and high-hardness multi-element alloy titanium-based composite material TMC8
[0148] The high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment includes a matrix and a reinforcement phase, and the matrix alloy includes the following elemental components in mass percentage: Al 5.5%, Nb 2.5%, Fe 1.7%, Mo 1.45%, V 1.35%, Zr 1.2% and the balance is Ti.
[0149] The reinforcing phase is TiB and La 2 O 3 The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 5.0%, and La 2 O 3 The mass percentage is 0.5%.
[0150] The method for preparing the high-strength and high-hardness multi-component alloy titanium-based composite material described in this embodiment comprises the following steps:
[0151] (S1) according to the mass percentage of the elemental components of the matrix, raw materials including sponge titanium 785.91g, high-purity aluminum 43.471g, niobium titanium alloy (Ti-53Nb) 44.58g, iron particles 16.07g, vanadium aluminum alloy (Al-60V) 21.26g, titanium molybdenum alloy (Ti-32Mo) 42.82g, and sponge zirconium 11.34g are added, and then reinforcing phase titanium diboride 29.55g and lanthanum oxide 5g are added to obtain an alloy material; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB 2 =2TiB.
[0152] (S2) melting the alloy material by vacuum suspension smelting to obtain a titanium-based composite ingot;
[0153] The specific process of the vacuum suspension melting comprises the following steps:
[0154] (S2.1) placing alloy material in a crucible;
[0155] (S2.2) The vacuum in the vacuum water-cooled copper crucible suspension melting furnace is pumped to 4×10 -2 Pa, fill with argon 0.09MPa, turn on the power;
[0156] (S2.3) melting at 80kw, 100kw, 120kw and 140kw for 6 minutes respectively, and then refining at 140kw for 6 minutes;
[0157] (S2.4) The alloy is turned over and the melting and refining process is repeated 7 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0158] (S3) First, a cylindrical casting is cut out on the titanium-based composite material ingot by wire cutting; then, a Ti-1200 high-temperature anti-oxidation coating is evenly applied on the surface of the casting to reduce high-temperature oxidation. After drying, the casting is placed in a hot rolling mill for five hot rolling passes, wherein the starting rolling temperature of each hot rolling pass is 1200K, the final rolling temperature is 1175K, and an intermediate annealing treatment is performed between the hot rolling passes at a temperature of 1190K for 6 hours. The hot rolling deformation is 70%, and a hot-rolled rod of a high-strength and high-hardness multi-element alloy titanium-based composite material is obtained, which is numbered TMC8.
[0159] Example 9: The hot rolling deformation of TMC0-TMC6 was changed from 80% to 60%
[0160] The steps and process parameters of this embodiment are the same as those of Comparative Example 1 and Examples 1-6, except that: the number of hot rolling passes in the hot rolling process of Comparative Example 1 and Examples 1-6 is four, the hot rolling deformation is changed to 60%, and the hot-rolled titanium-based composite material bars obtained are numbered TMC0-60, TMC1-60, TMC2-60, TMC3-60, TMC4-60, TMC5-60, and TMC6-60, respectively, to explore the influence of deformation on the performance of titanium-based composite materials.
[0161] Example 10 Hot rolled bars of TMC0-TMC6 were ion nitrided
[0162] The hot-rolled bars of TMC0-TMC6 are placed in a glow ion nitriding furnace, and the voltage is set to 450V, the temperature to 520℃, and the heating rate to 25℃ / min. Then nitrogen is introduced. When the temperature reaches 520℃, hydrogen is introduced into the glow ion nitriding furnace (according to the volume ratio of nitrogen to hydrogen of 1:3) until the pressure reaches 250Pa. Ion nitriding is carried out for 18 hours. After cooling, TMC0-TMC6 bars after ion nitriding treatment are obtained.
[0163] Example 11 Ion nitriding treatment of hot-rolled bars of TMC7 titanium-based composite materials
[0164] The hot-rolled rod of the TMC7 titanium-based composite material is placed in a glow ion nitriding furnace, and the voltage is set to 400V, the temperature is set to 900°C, and the heating rate is set to 20°C / min. Then nitrogen is introduced. When the temperature reaches 900°C, hydrogen is introduced into the glow ion nitriding furnace (according to a nitrogen to hydrogen volume ratio of 1:3) until the pressure reaches 200Pa. Ion nitriding is carried out for 5 hours. After cooling, the titanium-based composite material after ion nitriding treatment is obtained.
[0165] Example 12 Hot-rolled rod of TMC8 titanium-based composite material was subjected to ion nitriding treatment
[0166] The hot-rolled bars of the TMC8 titanium-based composite material were placed in a glow ion nitriding furnace, and the voltage was set to 500 V, the temperature to 400 °C, and the heating rate to 25 °C / min. Nitrogen was then introduced. When the temperature reached 400 °C, hydrogen was introduced into the glow ion nitriding furnace (according to a nitrogen to hydrogen volume ratio of 1:3) until the pressure reached 250 Pa. Ion nitriding was performed for 20 hours, and after cooling, the titanium-based composite material after ion nitriding treatment was obtained.
[0167] Performance Testing
[0168] (1) Mechanical properties
[0169] from Figure 2 As shown in Table 2, Table 3 and Table 4, the comprehensive mechanical properties of the hot-rolled titanium-based composite materials are improved compared to the cast state, especially the hardness is greatly improved, and the strength is also significantly improved. In addition, when the deformation is 60%, the tensile strength of TMC3-60 is higher, indicating that reducing the hot rolling deformation will be beneficial to the improvement of tensile strength. When the deformation is 80%, the hardness of TMC4 is higher.
[0170] Table 2 Comparison of cast mechanical properties of TMC0-TMC6
[0171]
[0172] Table 3 Hot rolling
[0173]
[0174]
[0175] Table 4 Mechanical properties of titanium matrix composites with hot rolling deformation of 60%
[0176]
[0177] (2) Organizational characteristics
[0178] Figure 3 The optical microscope images of TMC0-TMC6 in the casting state show that the structures of TMC0, TMC2, TMC4 and TMC5 are Widmanstatten structure, while the structures of TMC1, TMC3 and TMC6 are basketweave structure. Therefore, TMC2, TMC4 and TMC5 have stronger hardness.
[0179] Figure 4 The SEM images of TMC0-TMC6 cast state show that the distribution of the reinforcement phase in the alloy matrix is not uniform, and there are long rod-shaped, granular and block-shaped reinforcement phases. The size of the reinforcement phase varies, and the length of the large-sized reinforcement phase can reach tens of μm.
[0180] Figure 5The optical microscope images of TMC0-TMC6 after hot rolling show that after hot rolling, TMC2 and TMC3 are equiaxed structures, TMC0, TMC1, and TMC4 are dual-state structures, TMC5 is Widmanstatten structure, and TMC6 is basketweave structure. Increasing the content of the reinforcing phase can increase the hardness, and the type of reinforcing phase has little effect on the hardness and tensile strength.
[0181] Figure 6 The SEM images of TMC0-TMC6 after hot rolling show that the size of the reinforcement phase of the titanium-based composite material after hot rolling is reduced compared with the cast state. Compared with other composite materials, the size of the reinforcement phase of TMC3 is smaller.
[0182] Figure 7 The optical microscope images of TMC0-60 to TMC6-60 show that when the hot rolling deformation is 60%, TMC0-60 is a Widmanstatten structure, TMC1-60 is a dual-state structure, and TMC2-60 to TMC6-60 are basketweave structures. The structure after 60% deformation is quite different from that after 80% hot rolling deformation. Taking TMC3-60 as an example, the equiaxed structure corresponding to 80% deformation is transformed into a basketweave structure corresponding to 60% deformation. This is mainly because a larger deformation is conducive to promoting recrystallization, thus resulting in a higher tensile strength corresponding to a small deformation.
[0183] Figure 8 The SEM images of TMC0-60 to TMC6-60 show that the reinforcement phase is unevenly distributed in the matrix and has different sizes. The main forms are long rods, short rods, nearly spherical, polygonal, etc. Compared with the cast state, the size of the reinforcement phase is reduced to a certain extent. Compared with the titanium-based composite material with 80% deformation, the titanium-based composite material with 60% deformation corresponds to a finer reinforcement phase, indicating that increasing the deformation amount can effectively crush the reinforcement phase.
[0184] (3) Properties of TMC0-TMC6 before and after ion nitriding
[0185] It can be seen from Table 5 that the hardness of hot-rolled TMC0-TMC6 is significantly improved after ion nitriding treatment.
[0186] Table 5 Comparison of hardness (HRC) of TMC0-TMC6 before and after ion nitriding treatment
[0187]
[0188] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application. The specification and embodiments are to be regarded as exemplary only, and the present application is not limited to the precise structures described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof.
Claims
1. A method for preparing a high-strength and high-hardness multi-element alloy titanium-based composite material, characterized in that: The steps include: (S1) preparing raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy material; (S2) obtaining a titanium-based composite ingot by vacuum suspension smelting the alloy material; (S3) hot rolling the titanium-based composite material ingot in the (α+β) phase region for at least four times to obtain a high-strength and high-hardness multi-element alloy titanium-based composite material.
2. The preparation method according to claim 1, characterized in that: The high-strength and high-hardness multi-element alloy titanium-based composite material is subjected to ion nitriding treatment, and the hardness of the obtained titanium-based composite material is further improved.
3. The preparation method according to claim 1, characterized in that: In step (S1), the element composition of the matrix is Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo 1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the balance is Ti; The reinforcement phase includes La2O3 and also includes TiB and / or TiC.
4. The preparation method according to claim 1, characterized in that: The mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
5. The preparation method according to claim 1, characterized in that: In step (S2), the specific process of the vacuum suspension smelting includes the following steps: (S2.1) placing alloy material in a crucible; (S2.2) evacuating the vacuum water-cooled copper crucible suspension smelting furnace, filling it with argon, and turning on the power supply; (S2.3) smelting at a power of 70 to 140 kW, and then refining at a power of 130 to 140 kW; (S2.4) The alloy is turned over and the melting and refining process is repeated for at least 5 times. After the refining is completed, the furnace is naturally cooled, the air is released and the furnace is taken out to obtain a titanium-based composite ingot.
6. The preparation method according to claim 1, characterized in that: In step (S3), the starting rolling temperature of each hot rolling pass is 1200-1250K, and the final rolling temperature is 1175-1200K.
7. The preparation method according to claim 1, characterized in that: In step (S3), an intermediate annealing treatment is performed between hot rolling passes at a temperature of 1190 to 1220 K for 0.5 to 6 hours.
8. The preparation method according to claim 3, characterized in that: In step (S1), the elements Ti, Al, Nb, Fe, Mo, V, and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy, and sponge zirconium, respectively; TiB, TiC, and La2O3 in the reinforcement phase are added in the form of titanium diboride, graphite powder, and lanthanum oxide, respectively.
9. The preparation method according to claim 8, characterized in that: The titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown in the following formula: Ti+TiB2=2TiB, Ti+C=TiC.
10. The preparation method according to claim 5, characterized in that: The vacuum degree in the step (S2.2) is 3.5×10 -2 ~4×10 -2 Pa, filled with argon 0.07~0.09MPa.
11. The preparation method according to claim 5, characterized in that: In the step (S2.3), the smelting process is carried out at powers of 70-80kw, 90-100kw, 110-120kw, and 130-140kw in sequence, and then refined at a power of 130-140kw.
12. A high-strength and high-hardness multi-component alloy titanium-based composite material prepared by the method according to any one of claims 1 to 11, characterized in that: It comprises a matrix and a reinforcement phase, wherein the matrix comprises Al 5-5.5%, Nb 2-2.5%, Fe 1.5-1.7%, Mo 1.4-1.45%, V 1.25-1.35%, Zr 0.8-1.2% and the remainder Ti; The reinforcement phase includes La2O3 and also includes TiB and / or TiC. The mass percentage of the reinforcement phase in the titanium-based composite material is 3.02-5.5%.
Citation Information
Patent Citations
Preparation method of high-strength high-elasticity modulus titanium matrix composite
CN103436736A
Short-time high-temperature high-strength titanium alloy and preparation method and application thereof
CN116144982A
High-hardness wear-resistant titanium alloy and precision casting method thereof
CN116411204A
Medical high-temperature-resistant high-strength ultrasonic osteotome titanium alloy and bar as well as preparation method and application thereof
CN118028657A
Boron-containing pure titanium material, and method of manufacturing the same
JP2012077346A